Initiating advanced laparoscopic surgery in a medical college hospital with basic laparoscopic set up: Is it feasible and safe? - Thapa, PB (Kathmandu University Medical Journal, 2010)
Background: Laparoscopic surgery involves performing surgery through small incisions in abdominal wall to get access. Primary goal of this procedure is to achieve good cosmetic outcome, reduced post operative pain, early recovery and reduced hospital admission. Objective: The main objective of this study is to see the feasibility and benefit of performing advance laparoscopic surgery in a place where basic laparoscopic surgery is done and to share my experience while performing it. Materials and methods: A retrospective study of case sheets and discharge summary from 1st May 2008 till 1st August 2009 was done. Altogether eight patients underwent different advanced laparoscopic procedure. Cases done for the first time in the institute and those done by himself were only included. Technical feasibility, use of devices like harmonic scalpel, need for incision extension, operative time, blood product requirement, ambulation and enteral feed, post operative hospital stay and patients satisfaction regarding minimal scars were assessed. Result: Total eight patients underwent advance laparoscopic surgery. There were two common bile duct (CBD) exploration of which one was transcystic exploration, one total laparoscopic abdominoperineal resection (APR) for rectal cancer, one laparoscopic assisted right hemicolectomy for carcinoma ceacum, one laparoscopic assisted sigmoid colectomy for recurrent sigmoid volvulus, two laparoscopic right nephrectomy for non functioning right kidney, one retroperitoneal pyelolithotomy and one laparoscopic assisted splenectomy for massive splenomegaly with haemolytic anaemia. All procedures were technically feasible with basic laparoscopic instruments. However harmonic scalpel was required for splenectomy due to difficult hilum dissection. Ureteroscope was used as a choledochoscope in CBD exploration. Blood transfusion was required only in patient with low preoperative haemoglobin. Early ambulation and enteral feed was done within 24 hours in all and within 48 hours in patients who had bowel anastomosis. Post operative hospital stay was 5-8 days. Cosmetic scar was appreciated by all. Although long term oncological outcome is yet to come in malignancy case, biopsy report of laparoscopic APR identified 13 nodes which shows complete nodal dissection on oncological principal basis. Conclusion: Advanced laparoscopy is feasible, safe and effective in the hand of surgeons performing basic laparoscopic surgeries with guidance from surgeons who have long experience on same procedures but by open method. Key words: Advanced Laparoscopic Surgery DOI: 10.3126/kumj.v8i2.3572 Kathmandu University Medical Journal (2010), Vol. 8, No. 2, Issue 30, 261-264